Performance assessment of junior public health nurse in maternal and child health services in a district of Kerala, India - Achampattu Mridulal, Kariyarath Cheriyath Premarajan, Saya Ganesh Kumar (International Journal of Advanced Medical and Health Research, 2015)
Background: Performance assessment of health services provided to maternal and child population is an important area of concern especially in developing countries including India. Aim: This study was conducted to assess the performance of Junior Public Health Nurses (JPHN) on services provided to maternal and child health at sub-centers in Malappuram district of Kerala, India. Methods: Maternal and child health services were assessed based on record analysis and interviewing JPHN in 30 randomly selected sub-centers using a predesigned questionnaire prepared according to Indian Public Health Standards for sub-centers. The work performed by the JPHNs was graded as excellent, very good, good, satisfactory, and poor based on the standard guidelines. Results: Population covered by the 30 JPHNs at their sub-centers ranges from 5050 to 9869. Services were excellent in all the sub-centers for tetanus toxoid immunization and institutional deliveries. Although antenatal care (ANC) registration was excellent in 70% of the sub-centers, it was poor for the 1 st trimester ANC registration in 50% of sub-centers. In the case of referral services and postnatal care (PNC), 27% and 33% of the centers were excellent, respectively. 50% of the centers have had poor performance in PNC. Detection of beneficiaries for immunization by JPHNs was excellent in 60% of the sub-centers. Measles and full immunization coverage was poor in 40% of sub-centers. Around 77% JPHNs attended in-service training, and 90% of them could prepare sub-center annual action-plan. Conclusion: There is a variation in performance of JPHNs at a sub-district level which highlights the importance of further studies to elucidate the factors associated with it.